2017
DOI: 10.3389/fmicb.2017.01564
|View full text |Cite
|
Sign up to set email alerts
|

Tetrathionate and Elemental Sulfur Shape the Isotope Composition of Sulfate in Acid Mine Drainage

Abstract: Sulfur compounds in intermediate valence states, for example elemental sulfur, thiosulfate, and tetrathionate, are important players in the biogeochemical sulfur cycle. However, key understanding about the pathways of oxidation involving mixed-valance state sulfur species is still missing. Here we report the sulfur and oxygen isotope fractionation effects during the oxidation of tetrathionate (S4O62−) and elemental sulfur (S°) to sulfate in bacterial cultures in acidic conditions. Oxidation of tetrathionate by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 92 publications
(196 reference statements)
1
11
1
Order By: Relevance
“…However, water is not the only factor determining the δ 18 O of newly formed sulphate. According to Balci et al (2017) and Houle et al (2014), the δ 18 O of newly formed sulphate (δ 18 O sulphate(formed) ) is given by Equation 7:…”
Section: Water Source Effects On Soil Sulphate Oxygen Isotope Signamentioning
confidence: 99%
See 2 more Smart Citations
“…However, water is not the only factor determining the δ 18 O of newly formed sulphate. According to Balci et al (2017) and Houle et al (2014), the δ 18 O of newly formed sulphate (δ 18 O sulphate(formed) ) is given by Equation 7:…”
Section: Water Source Effects On Soil Sulphate Oxygen Isotope Signamentioning
confidence: 99%
“…The ε 18 O sulphate-water values were proposed by Llyod (1967) at 0‰ and Balci et al (2007) for S 0 corresponds to the ε 18 O sulphate-air value of −10.8‰ as proposed by Balci et al (2007) for inorganic S oxidation. However, fractionation factors can change in dependence on the experimental conditions such as temperature or pH (Balci et al, 2017;Smith, Jim Hendry, Wassenaar, & Lawrence, 2012). Therefore, different types of organic fertilizers might result in variable fractionation coefficients.…”
Section: Water Source Effects On Soil Sulphate Oxygen Isotope Signamentioning
confidence: 99%
See 1 more Smart Citation
“…Our earlier short-term study already reported that vetiver can remove SO 4 2- . Oxidation-reduction pathways can transform SO 4 2into elemental or mixed-valence-state forms of sulfur (Chen et al, 2016b;Balci et al, 2017).…”
Section: Effects Of Vetiver Rafts and Vetiver Plants On Ph Conductivmentioning
confidence: 99%
“…Compounds like thiosulfate and tetrathionate have been detected in oxidized sulfide minerals and are thought to have major roles in the sulfur cycle of AMD (Balci et al, 2017). Conversion of SO 4 2to sulfide through dissimilatory sulfate reduction (DSR) is considered a major initial step in detoxification (Chen et al, 2016b;Saad et al, 2016;Balci et al, 2017). Sulfides can then precipitate in the presence of metals, such as Fe from AMD (Chen et al, 2016b , and microbially reduced sulfides .…”
Section: Effects Of Vetiver Rafts and Vetiver Plants On Ph Conductivmentioning
confidence: 99%